1983
DOI: 10.1152/ajpheart.1983.244.3.h444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caloric restriction on cardiac reactivity and beta-adrenoceptor concentration

Abstract: The effect of a 21-day program of caloric restriction on cardiac reactivity and beta-adrenoceptor number was investigated in male Sprague-Dawley rats. Rats on the restricted diet (Restricted) exhibited significant decreases in body weight, epididymal fat pad, and retroperitoneal fat pad weight as well as the percent of body fat represented by these adipose tissue depots when compared with rats fed ad libitum (Fed). Fed rats exhibited significantly increased total heart weight and total heart protein, but the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
5

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
1
14
0
5
Order By: Relevance
“…Earlier studies have shown that ␤-adrenergic sensitivity was enhanced in adipose tissue (5) and reduced in vascular smooth muscle (18). In the atria, short-term FR (11,18), but not protein deficiency (3), enhanced the sensitivity to ␤-adrenergic stimulation. In the isolated working heart, protein-calorie malnutrition increased both the sensitivity and responsiveness to ␤-adrenergic stimulation (13).…”
Section: H2339 Calorie Restriction and Cardiac Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that ␤-adrenergic sensitivity was enhanced in adipose tissue (5) and reduced in vascular smooth muscle (18). In the atria, short-term FR (11,18), but not protein deficiency (3), enhanced the sensitivity to ␤-adrenergic stimulation. In the isolated working heart, protein-calorie malnutrition increased both the sensitivity and responsiveness to ␤-adrenergic stimulation (13).…”
Section: H2339 Calorie Restriction and Cardiac Mechanicsmentioning
confidence: 99%
“…Not all changes induced by FR, however, enhance the aging phenotype. Short-term FR (11,18) increased the inotropic response to ␤-adrenergic stimulation in the atria. It also increased the inotropic and chronotropic responsiveness of the isolated working heart preparation to ␤-adrenergic agonists (13).…”
mentioning
confidence: 91%
“…While some cardiovascular data arc available for each model reviewed, the spontaneously obese rat has been most extensively characterized. Biochemical adaptations of the myocardium to exper imental obesity have been reported [26,27,47], but this area has not been investigated extensively. The combined effects of obesity and hypertension upon the heart have been observed recently in the aorticcoarcted, obese rat, which may serve in the future as a useful model for investigating the basis of heart fail ure that occurs when these disorders arc observed concurrently in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Of initial importance was the ability of the cardiac tissue to de velop contractile force through catechol amine stimulation, especially since the obese human heart exhibits reduced contractile in dices, often leading to cardiac failure [25]. Through a combination of in vitro analyses, cardiac (3-adrenoceptor concentration (Bmax) and affinity, as well as cardiac reactivity to exogenous isoproterenol were determined [26]. Obese rats exhibited increased cardiac weight and total cardiac protein as discussed earlier, but ventricular Bmax was unaffected [26].…”
Section: Time Period Monthsmentioning
confidence: 99%
See 1 more Smart Citation